Å‹-ASSIMILATION IN VOICE DENTAL VELAR VOICE SOUND IN PAPUAN MALAY - Renhoard, Nathalia; Mahdi, Sutiono (Jurnal Bahasa Inggris, 2017)
This paper is meant to discuss correct phonological solutions to assimilation segment at the underlying level of accent in Papuan Malay. The methodology: to explain for ?-assimilation in Papuan Malay, the researcher refers to Halle (2017) theoretical views on Generative Phonology. The ?-sound appears in Papuan Malay, if a word is ended by a consonant /n/ dental velar voice results the process of ?-sound in the environment of cluster in the word-middle and word finally (the tow core of syllablles) and also after vowel. One example, word Teminabuan [t?min?bu?n] (one of village in Papua) is uttered as Teminabuang [t?min?bu??].The conclusions: it is explicit that the ?-assimilation are not only syntactically motivated due such as a phrasal to the occurrence of a word entity in the structure but also phonologically, a word may because there are certain specific environments in which such process take place.Key Words: Phonological rules, ?-assimilation, Papuan Malay.